Prevalência e fatores associados à autopercepção negativa de saúde em adolescentes da região Norte do Brasil (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Prevalence and the factors associated with adolescents’ negative self-perception of health in the Northern region of Brazil